Investigation of EEG Parameters in Virtual Reality Puck Shooting Task in Hockey Players and Freestyle Wrestlers - I.S. Polikanova; S.V. Leonov (Вестник Московского университета. Серия 14: Психология)
Background. Very scarce works are devoted to the study of hockey players' brain activity, which is connected, among other things, with the large amount of motor activity in athletes and the complexity of EEG registration. Objective. The aim of the study was to investigate electroencephalographic markers (in alpha, beta, and theta EEG bands) during a puck kicking task of varying difficulty under virtual reality conditions in ice hockey players compared to freestyle wrestlers. Methods. The previously developed VR-PACE technology was used for the study, which allows practicing puck reflection skills in hockey in a virtual scene. In the study, pucks were presented in blocks (five blocks in total), the difficulty increased from block 1 to block 4, in block 5 the subjects only observed the pucks. EEG recordings were made using a wireless electroencephalograph BrainScanner V3.1 (research edition) by “NeuroDrive” throughout the entire task, analyzed by 20-second segments in each block and in each of the backgrounds (before and after). Twenty-two male subjects (average age=20, SD=2.4 years) participated in the study. Results. The results showed significant differences between the groups, as well as significant within-group differences between the “before” and “after” conditions of the experiment in terms of the Individual Alpha Frequency (IAF), as well as the average and total power of theta, alpha, and beta rhythms. The overall trend in both groups is similar (after the experiment, there is a decrease in IAF, an increase in alpha rhythm power in central and parietal electrodes, and a decrease in occipital electrodes; a decrease in theta rhythm power in frontal and occipital electrodes; and a decrease in beta rhythm across all electrodes). However, the hockey group exhibits significantly more pronounced shifts in EEG, indicating greater alertness and attention (higher powers of theta, alpha, and beta rhythms both before and after the experiment), as well as greater relaxation (higher power of mu rhythm after the experiment). Conclusions. The study examined the electroencephalographic correlates (IAF, power in the alpha, beta, and theta frequency bands of EEG) in hockey players and freestyle wrestlers while performing a task of deflecting a puck in virtual reality (VR). The dynamics of the EEG indicators indicate more efficient brain function in hockey players when performing the puck reflection task in a virtual reality setting, confirming the hypothesis of neural efficiency.